Analysis of Municipal Solid Waste Generation and Composition at Administrative Building Cafe in Universiti Putra Malaysia: A Case Study - Abd Hamid, Khairul Bariyah; Ishak, Mohd Yusoff; Abu Samah, Mohd Armi (HARD Publishing, 2015)
Increasing solid waste is one of the most crucial environmental problems in Malaysia. Improper management of solid waste will cause many problems. Increasing solid waste, lack of segregation from the source, and lack of knowledge and awareness about recycling have only worsened the problem.Knowledge of solid waste generation and composition is necessary for accurate decision making in the management strategy of municipal solid waste.The objectives of this study were to measure solid waste generation and analyse and compare the composition of solid waste in two different cafes at Universiti Putra Malaysia.